Dietary supplementation with L-citrulline improves amino acid composition and broiler performance, and modulates gut microbiota - Ma, Yan; Liu, Tingting; Chen, Shuaihu; Shen, Hong; Wang, Jungang (Frontiers in Microbiology, 2025)
Poultry lacks carbamoyl phosphate synthetase, which is a key enzyme in the endogenous synthesis of arginine, thus poultry must obtain arginine from their diet. Citrulline (L-Cit), as a precursor of arginine, produces the same biological effects as arginine, and may even be more effective. In these experiments, we discovered that the addition of L-Cit significantly increased production performance, antioxidant and immune properties, and modulated the intestinal microbiota. The study involved 240 1-day-old male yellow-feathered broilers randomly assigned to one of four treatment groups: control (CON), 0.5% L-Cit, 1% L-Cit, and 1.5% L-Cit, with 10 replicates per group and six birds per replicate. The feeding trial lasted for 63 days. The body weight at 42 days and 63 days, as well as the average daily weight gain from day 1 to 63, increased linearly and quadratically with the addition of L-citrulline. The plasma concentrations of citrulline, ornithine, and arginine increased linearly with the dose of L-Cit. L-citrulline increased total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) levels and decreased interleukin-1β (IL-1β), IL-6, and tumor necrosis factor alpha (TNF-α). Dietary addition of 1% L-Cit also significantly altered the overall composition of the broiler intestinal microbiota, increasing the relative abundance of Prevotellaceae_UCG-001 while reducing the relative abundance of Synergistota and Campylobacterota. This indicates that L-Cit can enhance the production performance of broilers, and improve antioxidant activity and immune functions, thereby protecting intestinal health. The optimum dietary amount of L-Cit is 1 to 1.5%.